Antimicrobial Susceptibility to 27 Drugs and the Molecular Mechanisms of Macrolide, Tetracycline, and Quinolone Resistance in Gemella sp. - Michiko Furugaito; Yuko Arai; Yutaka Uzawa; Toshinori Kamisako; Kohei Ogura; Shigefumi Okamoto; Ken Kikuchi (MDPI AG, 2023)
Gemella is a catalase-negative, facultative anaerobic, Gram-positive coccus that is commensal in humans but can become opportunistic and cause severe infectious diseases, such as infective endocarditis. Few studies have tested the antimicrobial susceptibility of Gemella. We tested its antimicrobial susceptibility to 27 drugs and defined the resistant genes using PCR in 58 Gemella strains, including 52 clinical isolates and six type strains. The type strains and clinical isolates included 22 G. morbillorum, 18 G. haemolysans (GH) group (genetically indistinguishable from G. haemolysans and G. parahaemolysans), 13 G. taiwanensis, three G. sanguinis, and two G. bergeri. No strain was resistant to beta-lactams and vancomycin. In total, 6/22 (27.3%) G. morbillorum strains were erythromycin- and clindamycin-resistant ermB-positive, whereas 4/18 (22.2%) in the GH group, 7/13 (53.8%) G. taiwanensis, and 1/3 (33.3%) of the G. sanguinis strains were erythromycin-non-susceptible mefE- or mefA-positive and clindamycin-susceptible. The MIC90 of minocycline and the ratios of tetM-positive strains varied across the different species-G. morbillorum: 2 µg/mL and 27.3% (6/22); GH group: 8 µg/mL and 27.8% (5/18); G. taiwanensis: 8 µg/mL and 46.2% (6/13), respectively. Levofloxacin resistance was significantly higher in G. taiwanensis (9/13 69.2%) than in G. morbillorum (2/22 9.1%). Levofloxacin resistance was associated with a substitution at serine 83 for leucine, phenylalanine, or tyrosine in GyrA. The mechanisms of resistance to erythromycin and clindamycin differed across Gemella species. In addition, the rate of susceptibility to levofloxacin differed across Gemella sp., and the quinolone resistance mechanism was caused by mutations in GyrA alone.